Efficacy of regular gargling with a cetylpyridinium chloride plus zinc containing mouthwash can reduce upper respiratory symptoms - Francisco Wilker Mustafa Gomes Muniz; Maísa Casarin; Natália Marcumini Pola; Cassiano Kuchenbecker Rösing; Taciane Menezes da Silveira; Francisco Hecktheuer Silva; Guilherme Azario de Holanda; Larissa Viana de Oliveira; Pedro Paulo de Almeida Dantas; Bernal Stewart; Zilson Malheiros; Carlos Benítez; et al. (PLoS ONE, 2025)
The posterior oral cavity serves as an entry point to both the digestive and respiratory systems. Optimal oral hygiene, particularly by means of gargling, has been shown to effectively reduce transmission and duration of respiratory illnesses (Clinical Trials registration: NCT06479226). Previous studies have demonstrated the effectiveness of gargling with an antimicrobial mouthwash in preventing the development of respiratory symptoms. To assess the impact of using an antimicrobial mouthwash for gargling in lowering the incidence of upper respiratory symptoms. A total of 150 individuals were recruited and randomly assigned to two groups: Control group: participants were requested to brush their teeth twice daily for two minutes using a commercially available fluoride toothpaste; and the Test Group, which also brushed their teeth twice daily for two minutes with a commercially available fluoride toothpaste and additional gargling twice a day with a mouthwash containing 0.075% Cetylpyridinium chloride and 0.28% Zinc Lactate (CPC+Zn). Individuals were asked to complete the WURSS-21 Daily Symptom Report over the course of the three-month study period using a diary. Regular gargling with the mouthwash containing CPC+Zn was efficacious in decreasing both the frequency (21.5% lower) and severity (11% lower) of respiratory symptoms throughout the study. Additionally, individuals that performed consistent cleansing of the posterior oral cavity with mouthwash had greater interference in daily activities, which should be further investigated. Adding gargling with a mouthwash containing 0.075% CPC + 0.28% Zn to a normal oral hygiene routine proves beneficial in lowering the incidence of upper respiratory symptoms commonly associated with cold and the flu. Trial registration: ClinicalTrials.gov NCT06479226